Avaliação do perfil toxicológico e antimicrobiano (in vitro) dos Canabinoides Canabidiol (CBD) e Δ-9 Tetrahidrocanabinol (THC) derivados da Cannabis sativa L. - Nascimento, Lidiane Silva do (2023)
This research aims to contribute to scientific efforts that seek to robustly understand the properties of C. sativa L. in the pharmacological context. The experiments aimed to evaluate toxicological aspects and pharmacological activities of the cannabinoids CBD and THC. A toxicological evaluation was carried out to examine the hemolytic potential of oils rich in cannabinoids, using human erythrocytes of types A-, B+ and O+. The oils were tested at concentrations of 50, 100, 200, 300 and 400 μg/mL. Hemolysis was quantified through the detection of hemoglobin released by red blood cells, measured at 540 nm by spectrophotometry. The results indicated that CBD, THC and CBD+THC oils did not cause hemolytic action above 8% in all concentrations and blood types tested. The oxidizing potential of cannabinoids revealed that CBD and THC were not able to promote significantly high levels of hemoglobin oxidation. Although methemoglobin values tended to increase with the concentration of the substance, these differences were not statistically significant. Regarding the osmotic fragility of red blood cells, the cannabinoids CBD and THC were evaluated to determine whether they protect against hemolysis in cells weakened by hypotonic solution. The results indicated that, although the percentages of hemolysis were reduced in some cases, the protection was of low effectiveness, even at the highest concentrations. Regarding antioxidant activity, the cannabinoids CBD and THC showed limited results in protecting against the oxidation of hemoglobin by phenylhydrazine. However, the mixture of the two cannabinoids presented a more powerful dynamic in protecting against oxidation. Antimicrobial activity was evaluated in 34 bacterial strains, 17 gram-positive and 17 gram-negative. Both cannabinoids have demonstrated the ability to inhibit bacterial growth, with CBD revealing greater efficacy by inhibiting 11 gram-positive and 4 gram-negative strains. THC inhibited the growth of 8 gram-positive and 1 gram-negative strains. However, it is important to note that the action of the molecules was bacteriostatic. The mixture of cannabinoids showed results similar to those obtained with the isolated compounds. Overall, we concluded that the cannabinoids CBD and THC exhibited low toxicity to human blood cells, exhibited limited antioxidant activity, and showed antimicrobial activity against pathogens of clinical importance, mainly as bacteriostatic agents.